A Comparative Study of Primary Adenoid Cystic and Mucoepidermoid Carcinoma of Lung - Kumar, Vivek; Soni, Parita; Garg, Mohit; Goyal, Abhishek; Meghal, Trishala; Kamholz, Stephan; Chandra, Abhinav Binod (Frontiers in Oncology, 2018)
Background Pulmonary mucoepidermoid carcinoma (PMEC) and pulmonary adenoid cystic carcinoma (PACC) are the two major types of primary salivary gland-type (PSGT) lung cancers. The demographic profile, clinicopathological features, and predictors of survival as an overall group have not been described for PSGT cancers of lung. Methods In this study, we analyzed demographic, clinical, and survival data from 1,032 patients (546 PMEC and 486 PACC) who were diagnosed of PSGT lung cancer in the Surveillance, Epidemiology and End Results database from 1973 to 2014. Results The PSGT constituted 0.09% of all lung cancers with age-adjusted incidence rate of 0.07 per 100,000 person-years and change of −32% from 1973 to 2014. The incidence of PMEC was slightly higher than PACC but there were no differences in the age and sex distribution. PACCs (55%) were significantly higher at trachea and main bronchus while PMECs were more common at peripheral lungs (85%). Most of the tumors were diagnosed at an early stage and were low grade irrespective of histology. As compared to PMEC, significantly higher number of patients with PACC underwent radical surgery and received adjuvant radiation. The 1- and 5-year cause-specific survival was 76.6 and 62.8%, respectively. On multivariate analysis, the survival was affected by age at diagnosis, tumor stage, histological grade, period of diagnosis, and surgical resection. The histology showed strong interaction with time and hazard ratio of patients with PACC was significantly worse than patients with PMEC only after 5 years. Conclusion The incidence of pulmonary PSGT cancer is 7 cases per 10 million population in the United States and is decreasing. There was no difference between demographic profile of patients with PMEC and PACC but pathological features were diverse. The difference in the survival of patients with the two histological types surfaced only after 5 years when survival of patients with PMEC was better than PACC.